2007
DOI: 10.1200/jco.2006.08.1620
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Phase III Trial of Panitumumab Plus Best Supportive Care Compared With Best Supportive Care Alone in Patients With Chemotherapy-Refractory Metastatic Colorectal Cancer

Abstract: Panitumumab significantly improved PFS with manageable toxicity in patients with chemorefractory colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
1,161
1
30

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,793 publications
(1,226 citation statements)
references
References 29 publications
34
1,161
1
30
Order By: Relevance
“…Jonker et al (2007) have evaluated, in a phase III clinical study, the role of cetuximab in patients with mCRC pretreated with an oxaliplatin-and irinotecan-based chemotherapy, showing an improvement in terms of OS of cetuximab plus best supportive care (BSC) respect to BSC alone (median OS of 6.1 vs 4.6 months, P ¼ 0.0046). Van Cutsem et al (2007) in a similar setting of patients have compared panitumumab plus BSC to BSC alone, showing that panitumumab prolonged the PFS (HR: 0.54; 95% CI: 0.44 -0.66, Po0.0001), with no difference in terms of OS. Despite the promising results, some issues could limit the use of these therapies in this setting of patients, such as the low impact on survival, the high cost of the drugs and the significant higher rate of grade 3 -4 adverse events with respect to BSC.…”
Section: Discussionmentioning
confidence: 99%
“…Jonker et al (2007) have evaluated, in a phase III clinical study, the role of cetuximab in patients with mCRC pretreated with an oxaliplatin-and irinotecan-based chemotherapy, showing an improvement in terms of OS of cetuximab plus best supportive care (BSC) respect to BSC alone (median OS of 6.1 vs 4.6 months, P ¼ 0.0046). Van Cutsem et al (2007) in a similar setting of patients have compared panitumumab plus BSC to BSC alone, showing that panitumumab prolonged the PFS (HR: 0.54; 95% CI: 0.44 -0.66, Po0.0001), with no difference in terms of OS. Despite the promising results, some issues could limit the use of these therapies in this setting of patients, such as the low impact on survival, the high cost of the drugs and the significant higher rate of grade 3 -4 adverse events with respect to BSC.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, resistance to cetuximab is common, and only 10% to 20% of patients truly benefit from the treatment. 4,5 Recently, it has been widely demonstrated that mutations in v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) codons 12 and 13 are major predictive biomarkers for resistance to cetuximab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] However, resistance to cetuximab is common, and only 10% to 20% of patients truly benefit from the treatment. 4,5 Recently, it has been widely demonstrated that mutations in v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) codons 12 and 13 are major predictive biomarkers for resistance to cetuximab treatment. [6][7][8][9] With reference to these findings, the European Medicines Agency 10 and, subsequently, the US Food and Drug Administration 11 have suggested that patients who have mCRC with KRAS codon 12 and codon 13 mutations should be excluded from cetuximab treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Blue spheroids exemplify factors/processes that are integral components of the corresponding feature and which are currently being targeted for cancer therapy; numbers refer to the following publications: (1) Tennant et al, 2010;(2) Desgrosellier and Cheresh, 2010;(3) Lessene et al, 2008 (4) Lane and Chabner, 2009;(5) Bianco et al, 2007;(6) Granchi et al, 2010;(7) Ferrara et al, 2004 and (8) Berdis, 2008. Novel paradigms for cancer therapy V Pavet et al phosphorylation and signaling, and thus inhibiting proliferation and promoting apoptosis. Panitumumab has been approved for the treatment of metastatic colorectal cancer showing preliminary activity in phase I/II clinical trials, and phase III clinical trials are currently ongoing (Van Cutsem et al, 2007). An interesting addition to this concept is that rexinoids exclusively exert their apoptotic action under conditions in which growth factor signaling is impaired (Shankaranarayanan et al, 2009), suggesting that the combination of both anticancer treatments might be an attractive strategy.…”
Section: Current Therapeutic Paradigms To Treat Cancermentioning
confidence: 99%